2011
DOI: 10.1038/hr.2010.269
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II induces human astrocyte senescence through reactive oxygen species production

Abstract: Angiotensin II (Ang II)-induced astrocyte senescence may be involved in cerebral ischemic injury and age-associated neurodegenerative disease. This study was conducted to determine the roles of reactive oxygen species production in Ang II-induced cellular senescence in cultured human astrocytes. Human astrocytes were stimulated with Ang II either with or without an angiotensin type 1 receptor blocker, CV11974, or an antioxidant, tempol. Application of Ang II to human astrocytes resulted in a concentration-depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 36 publications
0
27
0
Order By: Relevance
“…As concerning angiotensin II, it has been documented that in ageing its overexpression caused vascular senescence by mitochondrial and NADPH-dependent superoxide generation [18]. This mechanism was attenuated by mitochondrial electron transport chain or angiotensin type 1 receptor inhibitors [39,40]. Moreover, the infusion in rats of angiotensin II induced microvascular lesions in various vascular beds that resemble arteriolosclerosis [41].…”
Section: Introductionmentioning
confidence: 99%
“…As concerning angiotensin II, it has been documented that in ageing its overexpression caused vascular senescence by mitochondrial and NADPH-dependent superoxide generation [18]. This mechanism was attenuated by mitochondrial electron transport chain or angiotensin type 1 receptor inhibitors [39,40]. Moreover, the infusion in rats of angiotensin II induced microvascular lesions in various vascular beds that resemble arteriolosclerosis [41].…”
Section: Introductionmentioning
confidence: 99%
“…We also reported that aldosterone secretion induced by angiotensin II in astrocytes enhances neuronal damage due to angiotensin II [57]. Moreover, Liu et al showed that angiotensin II induces astrocyte senescence via superoxide production [25]. These findings of astrocyte dysfunction induced by angiotensin II also explain the crucial role of angiotensin II in dysfunction of the neurovascular unit (Figure 1).…”
Section: Effects Of Angiotensin II On Neurovascular Unitmentioning
confidence: 70%
“…On the other hand, Lanz et al showed that angiotensin II induced sustained central nervous system (CNS) inflammation via transforming growth factor- (TGF-) β in an experimental autoimmune encephalomyelitis (EAE) mouse model [24]. Furthermore, angiotensin II induced astrocyte senescence, which is involved in age-associated neurodegenerative disease via superoxide production [25]. In contrast, a centrally active ACE inhibitor, perindopril, was reported to prevent cognitive impairment in chronic central hypoperfusion rats [26] and Alzheimer disease model mice [27].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, we speculate that ROS generation and ROSinduced oxidative DNA damage may play a determinant role in TCDD-triggered astrocyte senescence. Coinciding with the notion, ROS have been reported to be crucial mediators of astrocyte senescence under different stressful conditions (Bitto et al, 2010;Liu et al, 2011). In addition, because ROS are involved in mitochondrial dysfunction, changes in mitochondrial biogenesis may also contribute to TCDD-induced premature senescence (Wan et al, 2014).…”
Section: Discussionmentioning
confidence: 97%